2022
DOI: 10.3389/fpsyg.2022.993224
|View full text |Cite
|
Sign up to set email alerts
|

Mobile-assisted vocabulary learning through the Shanbay App outside the classroom: Effects of self-regulation and peer scaffolding

Abstract: Recent decades have witnessed an increasing academic interest in mobile-assisted vocabulary learning. To explore the possible influencing factors on learning outcomes, this study aimed at examining the effects of self-regulation and peer scaffolding on mobile-assisted vocabulary learning among undergraduate students using Shanbay App beyond the classroom. To this end, altogether 71 intermediate-level English learners aged 17–19 years were chosen as participants, with 37 in the experimental group (with peer sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 114 publications
1
5
0
Order By: Relevance
“…This result corroborates the findings of other researchers that noted the importance of content and process scaffolding in the didactic and pedagogic design of e‐learning (Theelen & van Breukelen, 2022), and the effectiveness of mobile‐based scaffolding for supporting student performance in vocabulary and conversation comprehension in EFL settings (Fang et al, 2021). Moreover, this result concur with previous studies in terms of the positive influence of scaffolding on students' learning performance (Bacca‐Acosta et al., 2021; Belland et al, 2015; Belland, 2017; Guo et al, 2022; Jabeen et al, 2021; Lee et al, 2021). The positive effect of scaffolding on students' learning performance might be explained by the fact that scaffolding assist students to complete learning tasks that are outside of their current skills (in their zone of proximal development) and this has a positive impact on the students' learning.…”
Section: Discussionsupporting
confidence: 92%
“…This result corroborates the findings of other researchers that noted the importance of content and process scaffolding in the didactic and pedagogic design of e‐learning (Theelen & van Breukelen, 2022), and the effectiveness of mobile‐based scaffolding for supporting student performance in vocabulary and conversation comprehension in EFL settings (Fang et al, 2021). Moreover, this result concur with previous studies in terms of the positive influence of scaffolding on students' learning performance (Bacca‐Acosta et al., 2021; Belland et al, 2015; Belland, 2017; Guo et al, 2022; Jabeen et al, 2021; Lee et al, 2021). The positive effect of scaffolding on students' learning performance might be explained by the fact that scaffolding assist students to complete learning tasks that are outside of their current skills (in their zone of proximal development) and this has a positive impact on the students' learning.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is in parallel with Dindar et al’s finding ( 2020 ), in which the role of cooperation and competition were valued and proved to be effective at vocabulary learning. It is also supported by Guo et al’s finding ( 2022 ) that peer scaffolding significantly affects mobile vocabulary learning in terms of the days spent in vocabulary learning and the sum of words participants have learned. Noels et al’s study ( 2000 ) also found that when learners understand that their achievements benefit others, they will be more positive and motivated to accomplish even more.…”
Section: Discussionmentioning
confidence: 63%
“…The past decade has witnessed the rapid growth of educational technologies that were designed to enhance the four basic skills of listening, speaking, reading, and writing (Li et al, 2019 ). Based on the potential of apps for enhancing learners’ language abilities, several researchers (Burston, 2014 ; Guo et al, 2022 ; Kim & Kwon, 2012 ) identified the benefits of apps for language learning in Second Language Acquisition Theory (SLA) and Computer-Assisted Language Learning (CALL). As advocated in CALL theory by Meskill ( 1999 ), Oxford ( 1990 ), and Skehan ( 2003 ), apps offer opportunities to engage in interactive and meaningful tasks, promote collaborative, rewarding, and challenging tasks, and provide opportunities to produce the target language.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, as for the language learners themselves, they have to improve their self-regulation skills and motivation to engage in mobile-assisted language learning. The self-regulation skill is an important factor in autonomous learning ( Guo et al, 2022 ), and with children’s growing up, they have to turn the other-regulation into the self-regulation to become autonomous learners. In addition, students’ potential to actively pursue learning is shown by their motivation ( Dörnyei, 2019 , p. 25) and it serves as a foundation for subsequent engagement ( Martin, 2012 , p. 305).…”
Section: Discussionmentioning
confidence: 99%
“…Second, instructors should participate in the elementary students’ learning and monitor their learning behavior and results to provide immediate feedback and help. Due to their limited cognitive and self-regulated abilities, primary school students cannot carry the autonomous learning, thus instructors should provide them with self-regulation skills training ( Guo et al, 2022 ). Moreover, e-learning on the mobile-assisted devices makes a long psychological distance between students and their instructors, so teachers should participate in the whole learning process and monitor every student’s learning to change their teaching plan at any time and improve teaching effectiveness.…”
Section: Discussionmentioning
confidence: 99%